STRATEGI PEMBELAJARAN GURU PENDIDIKAN AGAMA ISLAM PADA ANAK BERKEBUTUHAN KHUSUS (AUTIS) DI SEKOLAH DASAR - Roina Barokatin,; Muhammad Nasir,; Fathul Jannah, (Inspiratif Pendidikan, 2023)
This research aims to explore and analyze the learning strategies used by Islamic Religious Education teachers in teaching children with special needs (autism) at YPPSB Elementary School (Prima Swarga Bara Education Foundation School) and SDN 004 Inklusi Sangatta, East Kutai Regency. Autism as a developmental disorder requires a special approach to learning to maximize children's potential.